Identifikasi Tantangan Adopsi E-commerce Pada Rumah Produksi Seulanga - Juwita, Juwita; Risa, Nursanty; Heru, Fahlevi (Universitas Diponegoro, 2017)
Peukan Bada is one of districts in Aceh Besar which directly opposite to Indian Ocean. This district had abundant marine fishery resources. In 2016 Seulanga home production has implemented E-commerce website to support their sales and promotion process, but after six months of releasing, there were no transcations occured. Fourth stage of E-commerce adoption in small and medium bussiness were achieved, if online transactions including ordering and payment have occured. To achieved that a reliable e-commerce website and organizational readiness was needed.The objective of this study was to identify the challenge of E-commerce adoption in Seulanga home production. It used Fishbone cause and effect with 4P approach (Price, Product, Place and Promotion). Data collecting using focus group discussion and site search testing technic. This research taken place in Peukan Bada district, Exactly in Lamteungoh village. This research had successfully identified causes that challenge the E-commerce adoption in seulanga home production, those were : product were unregistered, the fluctuative price, no managerial skilled staf and IT skilled staff, no promotion strategy applied and unsmart site search features. All those factors become barries of E-commerce adoption for seulanga home production, so Seulanga need external intervention to cope their continuity in bussiness